Odpowiedź :
a) I x>=0
x-2<1
x<3
x∈(-nieskończoność, 3)
II x<o
-x-2<1
-x<3 /*-1
x>-3
x∈(-3, +nieskończoność)
b)
I x>=0
3-5x-2>0
-5x>-1 /:-5
x<1/5
IIx<0
3+5x-2>0
5x>-1 /:5
x>-1/5
x-2<1
x<3
x∈(-nieskończoność, 3)
II x<o
-x-2<1
-x<3 /*-1
x>-3
x∈(-3, +nieskończoność)
b)
I x>=0
3-5x-2>0
-5x>-1 /:-5
x<1/5
IIx<0
3+5x-2>0
5x>-1 /:5
x>-1/5
Rozwiąż nierówność:
a) |x-2|<1
-1<x-2 ∧x-2<1
x>1 ∧ x<3
x∈(1,3)
b) |3-5x|-2 >0
|3-5x|>2
3-5x<-2 v 3-5x>2
-5x<-5 v -5x>-1
x>1 v x<1/5
x∈(-∞,1/5) u (1,∞)
a) |x-2|<1
-1<x-2 ∧x-2<1
x>1 ∧ x<3
x∈(1,3)
b) |3-5x|-2 >0
|3-5x|>2
3-5x<-2 v 3-5x>2
-5x<-5 v -5x>-1
x>1 v x<1/5
x∈(-∞,1/5) u (1,∞)
a) |x-2|<1
x-2<1 x-2>-1
x<3 x>1
x∈(1;3)
b) |3-5x|-2 >0
|3-5x|>2 |3-5x|>2
3-5x>2 3-5x<-2
-5x>-1 -5x<-5
x>0,2 x<1
x∈(0,2;1)
x-2<1 x-2>-1
x<3 x>1
x∈(1;3)
b) |3-5x|-2 >0
|3-5x|>2 |3-5x|>2
3-5x>2 3-5x<-2
-5x>-1 -5x<-5
x>0,2 x<1
x∈(0,2;1)